Case report: Three cases of systemic lupus erythematosus presenting primarily with massive ascites and significantly elevated CA-125 levels and a review of pseudo-pseudo Meigs’ syndrome in literature - Li, Qiyu; Tian, Bailing (Frontiers in Immunology, 2024)
We report three cases of systemic lupus erythematosus (SLE) that initially presented with significant pleural effusion, ascites, and marked elevation in Cancer Antigen 125 (CA-125) levels. After ruling out secondary causes such as tumors and infections, these cases were diagnosed as "pseudo-pseudo Meigs' syndrome" (PPMS). In addition, we reviewed 30 cases of PPMS reported since 2005, summarizing the pathogenesis, clinical characteristics, and treatment strategies associated with this condition. This review provides new insights and perspectives on the clinical management and understanding of PPMS.